Middle Level Teachers Quarantine, Teach, and Increase Self-Efficacy Beliefs: Using Theory to Build Practice During COVID-19 - Heather Rogers Haverback (Middle Grades Review, 2020)
During COVID-19, almost all schools have been transformed into something unlike what they were before. Teaching that was done in person is now done virtually, with little to no preparation. Middle level teachers may have been confident in how to teach their content in the classroom; however, this confidence may differ when teaching virtually. Using the four sources of self-efficacy theory, I analyze the importance of self-efficacy and how teachers can use the COVID-19 pandemic to build their self-efficacy beliefs while teaching during this unique time.
Keywords: self-efficacy beliefs; COVID-19; middle school; teacher education